The influence of the human factor on the deformation of buildings, structures and on the living conditions of residents - Samchenko, R.; Yukhymenko А. (Ways to Improve Construction Efficiency, 2019)
The real examples are given to the factors of gross ignoring the requirements and rules of building standards and the norms of exploitation that led to the emergency state of multisection houses and uncomfortable human habitation. The restoration of the emergency state of buildings was carried out using an innovative method developed to control the base deformations by perforating the base layer by drilling horizontal wells of variable parameters.